الواقعية الإسلامية في القصص الملايوية الحديثة المختارة = Islamic realism in selected modern Malay fictions - Ahmad, Muhammad Anwar; Sahrir, Muhammad Sabri (Global Business and Social Entrepreneurship (GBSE), 2018)
يدرس هذا البحث المذهب الأدبي الواقعي من المنظور الإسلامي. انبثق المذهب الواقعي عن النظرية الفلسفية التي تؤمن بأن الحياة مبنية على الشرّ، فالحياة في نظرها شرٌّ، ومحنة. فهذه النظرة مخالفة للنظرة الإسلامية للحياة. لذا يأتي هذا البحث ليدرس الاتجاه الأدبي الواقعي الذي يتمشى مع الإسلام وتعاليمه ومبادئه. وينطلق البحث من الأسس النظرية للمذهب الواقعي الإسلامي التي وضعها سيد قطب وطوّرها من بعده شقيقه محمد قطب. وفي سبيل إبراز هذا المذهب الأدبي الإسلامي يقوم البحث بتطبيق هذه الأسس النظرية على قصص مختارة من الأدب الملايوي الحديث، ويتم ذلك بتحليل نصوص هذه القصص وفقا لمنهج الواقعية الإسلامية. وتتجلى أهمية هذا البحث في إبراز مذهب أدبي إسلامي يتفق مع النظرة الإسلامية، ومن ثم استغلاله في دراسة النتاج الأدبي الإسلامي، ولعله بذلك سبيل الخروج من الاعتماد على العقلية الغربية المنحرفة. كما تكمن أهميته في المساهمة في مجال أسلمة الأدب. *********************************************************** This study examines the ideology of literary realism from the Islamic worldviews. The realism of literature was originated from the philosophical view which believes that life is established and developed from evilness and badness. Hence this ideology is in contradiction with Islamic worldviews. Therefore the research intends to study the literary realism that is in agreement with Islamic teachings and principles and consequently shed light upon the Islamization of literature. This study adopts the theoretical elements and fundamentals of Islamic literary realism introduced and created by Sayyid Qutb and later developed by his brother Muhammad Qutb. The research analyses the selected modern Malay fictions (5 short stories and 1 novel) using these theoretical elements and fundamentals which are in accordance with the Islamic realism ideology. The significance of this study lies in its effort to reveal and highlight Islamic literature ideology pursuant to Islamic worldview and consequently avoidance and keeping away from devious western ideology.